Understanding the Justification of Faith According to Apostle Paul and James - Melina Agustina Sipahutar (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
Understanding the concept of Justification by Faith is crucial for Christians, as it enables them to gauge their comprehension and application of this doctrine in their lives. Many Christians have yet to fully grasp this foundational aspect of their faith. This study aims to elucidate the true significance of Justification by Faith by comparing the perspectives of Paul and James, which at first glance, seem contradictory. This research employs a literature review approach, involving the identification, classification, and analysis of relevant literature on the topic of Justification by Faith according to Paul, James, and Calvin. The study involves a hermeneutical analysis of biblical texts, a comparison of theological perspectives, and a systematic organization of findings. Paul asserts that justification occurs through faith, independent of works, as an act of God's grace (Romans 3:28, 4:5). The law reveals human sinfulness and the need for divine justification through faith in Christ. James emphasizes that genuine faith is demonstrated through works (James 2:24). He argues that faith without works is dead and insists on the necessity of works as evidence of true faith. Calvin integrates both perspectives, emphasizing that justification by faith is inseparable from the process of regeneration by the Holy Spirit. He views faith as a gift from God that leads to good works, the fruit of genuine faith. Justification by Faith is an act of God that can only be achieved through His grace and the sacrifice of Jesus Christ (Romans 4:5; 5:6). Faith is rooted in the truth of God's revelation in Christ, culminating in belief in His crucifixion and resurrection. Both Paul and James agree that faith and works are essential in a genuine response to God, with good works being the inevitable result of true faith. This study underscores the interconnectedness of faith and works, aligning with Martin Luther's assertion that good works are the fruit of righteousness. The comprehensive understanding of Justification by Faith involves recognizing it as a divine act that provides hope for salvation through faith, a gift from God facilitated by the Holy Spirit (Ephesians 2:8; Galatians 5:22).